The poetics of impersonality : T.S. Eliot and Ezra Pound - Ellmann, Maud, 1954- (Edinburgh : Edinburgh University Press, 2013)
GBS_insertPreviewButtonPopup(['ISBN:9780748691296','ISBN:9780748691302']);In this classic work, Maud Ellmann examines T. S. Eliot's and Ezra Pound's criticism in terms of what she calls the 'poetics of impersonality'. She convincingly shows that Eliot's and Pound's attempts to overcome personality merely reinstated it in a new guise. And her superb and entirely original readings of the major poems of the modernist canon have earned a lasting place in criticism.Following an analysis of Eliot's relation to Bergson, Ellmann goes on to analyse Eliot's 'Tradition and the Individual Talent' and the later After Strange Gods, the early poems, The Waste Land, and Four Quartets. She then turns to Pound's Personae, particularly 'Mauberley', and the Cantos. Ellmann looks for the contradictions inherent in modernist literary ideology and deftly teases out their implications. Stylish and perceptive, this book marked the debut of a major literary critic, and it has as much resonance today as it did on first publication."
Frontmatter -- Contents -- Preface -- Principal Short Forms of Citation -- Acknowledgements -- Introduction: Ego Scriptor -- PART 1: T. S. ELIOT -- Chapter 1: The Loop in Time -- Chapter II: The Spider and the Weevil: Self and Writing in Eliot's Early Poetry -- Chapter III: The Waste Land: A Sphinx without a Secret -- Chapter IV: The Figure in the Four Quartets -- PART II: EZRA POUND -- Chapter V: "What part ob yu is deh poEM?" -- Chapter VI: The Erasure of History -- Coda -- Index
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Eliot, T. S. -- 1888-1965 -- Criticism and interpretation; Pound, Ezra, -- 1885-1972 -- Criticism and interpretation; Eliot, T. S. -- 1888-1965; Pound, Ezra, -- 1885-1972; Eliot, T. S. -- 1888-1965; Pound, Ezra -- 1885-1972; American poetry -- 20th century -- History and criticism; Self in literature; Identity (Psychology) in literature; Persona (Literature); Personality in literature; Poetry -- Psychological aspects; Poésie américaine -- 20e siècle -- Histoire et critique; Moi (Psychologie) dans la littérature.; Identité (Psychologie) dans la littérature.; Persona (Littérature); Personnalité dans la littérature.; Poésie -- Aspect psychologique; LITERARY CRITICISM -- Asian -- General; American poetry; Identity (Psychology) in literature; Persona (Literature); Personality in literature; Poetry -- Psychological aspects; Self in literature; Persönlichkeit; 1900-1999; Criticism, interpretation, etc